Some results on clique partitions of regular graphs - Escaner, Jona Kristine E. (Animo Repository, 1999)
This thesis discusses the partitioning of the edges of a simple connected 3-regular graph into a minimum number of complete subgraphs. This is called a minimum clique partition of the graph. Results are focused on various techniques in obtaining the exact values and bounds of the size of a minimum clique partition of a 3-regular graph. A discussion on externally adjacent vertices and separation of cliques is also presented.